A elasticidade da pobreza em relação ao crescimento e à desigualdade de renda no nordeste rural brasileiro de 1995 a 2009: uma análise comparativa - Lopes, Elinete Luisa (2011)
This work aims to analyze how the growth in average income and the change in inequality in income distribution have impacted rural poverty in the Northeast in the period 1995 to 2009. Under the approach in Kakwani (1993) e Duclos and Araar (2006), and under the assumption of log-normality of income per capita, exposed in Bourguignon (2002) and Hoffmann (2005), are calculated growth and inequality elasticities of poverty to FGT poverty measures in order to observe the behavior of the sensitivity of poverty to changes in average household income and the change in income distribution / Gini index. Concurrently, decomposes the changes in measures of poverty (proportion of poor) between growth and distribution components (first proposed by Datt and Ravallion, 1992) to assess the effect of weight change and the effect of income inequality change change on poverty. Regarding the estimation of elasticities of poverty and growth and inequality elasticities of the two methodologies used in this work - under the assumption of lognormal distribution of income and FGT measures under the by Kakwani (1993) andDuclos e Araar (2006) - though do not result in identical values, to corroborate same results, ie the long-term decline in rural poverty from 1995 to 2009 the Northeast and the greater sensitivity of the Northeast Rural Poverty, observed in this same period, income growth and change in inequality. The weight of growth and change in inequality in changing the Northeast rural poverty identified that most of the decline in rural poverty is linked to growth in average income. This result coincides with results found by Kraay (2005) for a group of countries